2017
DOI: 10.1002/dc.23639
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reproducibility of Nuclear/Cytoplasmic Ratio Assessments in Urinary Cytology Specimens

Abstract: Visual quantitation of N/C ratio showed only a fair correlation with actual N/C ratio with correlation decreasing with increasing N/C ratio. In the critical range, 0.5-0.7 N/C ratio both interobserver correlation and correlation with true N/C ratio may be insufficiently accurate for precise category assignment as used in the Paris System. Diagn. Cytopathol. 2017;45:107-112. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…Previous studies have shown that morphologists tended to overestimate the N:C ratio of urothelial cells, especially at N:C ratios close to cutoff values in TPS. 8,19,20 The current study data suggest that overestimating the N:C ratio would result in a slightly increased sensitivity but a markedly decreased specificity for HGUC. These data support the possible integration of automated digital imaging and/or computerized measurement of N:C ratios in urinary tract specimens, because the added precision could have a significant impact.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous studies have shown that morphologists tended to overestimate the N:C ratio of urothelial cells, especially at N:C ratios close to cutoff values in TPS. 8,19,20 The current study data suggest that overestimating the N:C ratio would result in a slightly increased sensitivity but a markedly decreased specificity for HGUC. These data support the possible integration of automated digital imaging and/or computerized measurement of N:C ratios in urinary tract specimens, because the added precision could have a significant impact.…”
Section: Discussionmentioning
confidence: 55%
“…This finding underscores the difficulty of determining such small changes in the N:C ratios when estimated by the human eye with light microscopy alone. Previous studies have shown that morphologists tended to overestimate the N:C ratio of urothelial cells, especially at N:C ratios close to cutoff values in TPS . The current study data suggest that overestimating the N:C ratio would result in a slightly increased sensitivity but a markedly decreased specificity for HGUC.…”
Section: Discussionmentioning
confidence: 57%
“…Hang et al used DIA to validate an N:C ratio cutoff of 0.5 for the AUC category, in keeping with TPS . To date, there have been no studies validating a N:C ratio cutoff value ≥0.7 for the HGUC and SHGUC categories Such a study is necessary, because Layfield and colleagues demonstrated that, at the critical N:C ratio (range, 0.5‐0.7), morphologists were less accurate and had moderate‐to‐poor interobserver concordance . Zheng et al also demonstrated that morphologists tended to overestimate N:C ratio in this range …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, humans are imprecise and not reproducible when performing visual quantitation. Layfield et al demonstrated that in the critical range of 0.5 to 0.7 for the N/C ratio, interobserver correlation and accuracy were insufficient to render a correct diagnosis …”
Section: Introductionmentioning
confidence: 99%